Smell and taste complaints - Hawkes, Christopher H (Butterworth-Heinemann, 2002)
This book provides guide to diagnosing and treating causes of disorders of smell and taste. Signs of problems with these two senses may be ignored by the patient or downplayed by the physician, but the disruption of the senses may be a first sign of serious illness. The wide range of conditions responsible for disorders of smell and taste make it difficult to determine the single underlying cause and to decide upon the best possible plan of treatment. Disorders of Smell and Taste will help physicians manage some of these patients thereby minimizing references to specialists